Enhanced electromagnetic microwave absorbing performance of carbon nanostructures for rams: a review - Sani, Yusuf; Azis, Raba'ah Syahidah; Ismail, Ismayadi; Yaakob, Yazid; Mohammed, J. (Elsevier, 2023)
Microwave absorbent materials (MAMs) are significant in a extensive range of civil and military applications, including national defense security, healthcare, electronic reliability, and anti-radar detection of war fighters, as information technology advances quickly, and recent years have seen an explosion in the investigation of nanomaterials for use in microwave absorption applications. Therefore, the creation of high-performance MAMs with thin thickness, low density, wide bandwidth, and robust absorption has attracted a lot of attention. MAMs nanocomposites are also used to make radar-absorbing materials (RAMs) for stealth aircraft. By combining RAMs with geometry, stealth technology (ST) reduces the reflection of electromagnetic waves back to a radar system. In this article, we discuss the fundamental theory, components, and mechanism of electromagnetic microwave absorption. It will be detailed how to improve the microwave absorbent materials' (MAMs') absorption characteristics. Metal-based composites often show significant efficacy in achieving desired magnetic and dielectric properties. This article gives a full look at the theory behind a few specific microwave absorbers made of ferrites and carbon-based composites with their method of preparation. Additionally, the classifications of microwave absorbers according to significant factors that influence the substance's basic microwave absorption characteristics are addressed. The effects of high-potential applications in microwave absorbent materials (MAMs) with thin thicknesses were also investigated. Additionally, this work offers a thorough overview of research on several microwave-absorbing materials and their basic microwave-absorbing processes, as well as dielectric loss, magnetic loss, dielectric/magnetic loss coupling, absorption bandwidth, and nanomaterial reflection loss (RL) values.